2006
DOI: 10.1111/j.1469-8137.2006.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium in plant defence‐signalling pathways

Abstract: Contents Introduction 250 Increases in free cellular [Ca2+]: an early and key event in plant defence signalling 251 Relationships between [Ca2+]cyt increases and defence‐signalling pathways 256 Calcium targets involved in plant defence reactions 258 Concluding remarks 262 Acknowledgements 263 References 263 Summary In plant cells, the calcium ion is a ubiquitous intracellular second messenger involved in numerous signalling pathways. Variations in the cytosolic concentration of Ca2+ ([Ca2+]cyt) couple a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
439
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 591 publications
(462 citation statements)
references
References 252 publications
(418 reference statements)
6
439
0
3
Order By: Relevance
“…These three parameters seem to be interrelated, thus suggesting the presence of downstream events that could converge (Bailey-Serres and Chang, 2005). Emerging evidence suggests that ROS-mediated activation of plasma membrane calcium (Ca 2+ ) channels is involved in plant signal transduction related to both biotic and abiotic stress and development events (for review, see Lecourieux et al, 2006). Previous results demonstrated the involvement of NADPH-oxidase-dependent H 2 O 2 production under O 2 deprivation response (Baxter-Burrell et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…These three parameters seem to be interrelated, thus suggesting the presence of downstream events that could converge (Bailey-Serres and Chang, 2005). Emerging evidence suggests that ROS-mediated activation of plasma membrane calcium (Ca 2+ ) channels is involved in plant signal transduction related to both biotic and abiotic stress and development events (for review, see Lecourieux et al, 2006). Previous results demonstrated the involvement of NADPH-oxidase-dependent H 2 O 2 production under O 2 deprivation response (Baxter-Burrell et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…NO has also been shown to induce an increase in the concentration of [Ca 2+ ] i in plant cells. NO may mobilize Ca 2+ from internal stores through the activation of ryanodine receptor (RYR)-like channels [15,17,40,41,[46][47][48] and plasma membrane Ca 2+ -permeable channels [40,41,47]. In the present study, our data showed that NO induced not only an increase in [Ca 2+ ] i in the protoplasts of maize leaves, which was sensitive to the plasma membrane Ca 2+ channel blocker LaCl 3 ( Figure 4A), but also increases in the expression of CaM1 ( Figure 5A) and the content of CaM in leaves of maize plants ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ions (Ca 2+ ) in the plants serve as secondary messengers mediating developmental responses, stress signaling, and herbivore attack [18]. After sensing aphid feeding, Ca 2+ sensors activate downstream defense signaling cascades by increasing expression of calmodulin, calmodulin binding proteins, and calcium-dependent protein kinases (CDPKs) [21]. The role of ROS in mediating herbivore attack by either chewing or piercing/sucking insects is unquestionable; however, the nature of response depends on type of herbivory and duration and intensity of feeding [4,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%